2021
DOI: 10.1021/acs.jproteome.1c00330
|View full text |Cite
|
Sign up to set email alerts
|

iBRET Screen of the ABCD1 Peroxisomal Network and Mutation-Induced Network Perturbations

Abstract: Mapping the network of proteins provides a powerful means to investigate the function of disease genes and to unravel the molecular basis of phenotypes. We present an automated informatics-aided and bioluminescence resonance energy transfer-based approach (iBRET) enabling high-confidence detection of protein−protein interactions in living mammalian cells. A screen of the ABCD1 protein, which is affected in X-linked adrenoleukodystrophy (X-ALD), against an organelle library of peroxisomal proteins demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 87 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…In peroxisomes, VLCFAs are mainly introduced as CoA through ABCD1-3 (Figure 5). Studies have shown that peroxisomal β-oxidation is dysfunctional after the deletion of ABCD1/ALDP in vivo, resulting in the expression levels of VLCFAs in both plasma and tissues being increased [97,98]. ABCD1 and ABCD2 share a high degree of sequence homology, except that ABCD2 plays a central role in the metabolism of monounsaturated and polyunsaturated VLCFAs, rather than saturated VLCFAs, and may be involved in the regulation of oxidative stress and DHA synthesis [99].…”
Section: Atp-binding Cassette (Abc)mentioning
confidence: 99%
“…In peroxisomes, VLCFAs are mainly introduced as CoA through ABCD1-3 (Figure 5). Studies have shown that peroxisomal β-oxidation is dysfunctional after the deletion of ABCD1/ALDP in vivo, resulting in the expression levels of VLCFAs in both plasma and tissues being increased [97,98]. ABCD1 and ABCD2 share a high degree of sequence homology, except that ABCD2 plays a central role in the metabolism of monounsaturated and polyunsaturated VLCFAs, rather than saturated VLCFAs, and may be involved in the regulation of oxidative stress and DHA synthesis [99].…”
Section: Atp-binding Cassette (Abc)mentioning
confidence: 99%
“…To determine a potential variant induced impairment on this process, interactions of wild-type and variant PEX26 with PEX6 were analyzed by means of bioluminescence resonance energy transfer (BRET). The application of BRET allows for interaction analyses in living cells in the physiological environment for the proteins investigated ( Gersting et al, 2012 ; Lotz-Havla et al, 2021 ). We investigated seven missense variants in PEX26 ( Figure 1A ), which all mapped to the PEX6 binding domain of PEX26 ( Weller et al, 2005 ; Nashiro et al, 2011 ; Fujiki et al, 2020 ) and three truncating or nonsense variants ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Protein-protein interactions were analyzed in living cells by bioluminescence resonance energy transfer (BRET) as described before ( Gersting et al, 2012 ; Hillebrand et al, 2012 ; Lotz-Havla et al, 2021 ). HEK293 cells were co-transfected by electroporation (Amaxa 96-well shuttle system, Lonza) with two genes of interest either fused to Rluc (donor) or YFP (acceptor) at an acceptor to donor ratio of 3:1.…”
Section: Methodsmentioning
confidence: 99%
“…There are several studies exhibiting the physical interaction between each of the ABCD transporters and other proteins. [44][45][46][47] Recently, several studies have shown that ABCD1 binds to proteins involved in lipid metabolism, protein/amino acid metabolism, peroxisomal matrix protein import, peroxisome organization, and membrane assembly. 47) These results indicate the involvement of ABCD1 in other processes in addition to the transport of VLCFA-CoA into peroxisomes.…”
Section: (See Below)mentioning
confidence: 99%
“…[44][45][46][47] Recently, several studies have shown that ABCD1 binds to proteins involved in lipid metabolism, protein/amino acid metabolism, peroxisomal matrix protein import, peroxisome organization, and membrane assembly. 47) These results indicate the involvement of ABCD1 in other processes in addition to the transport of VLCFA-CoA into peroxisomes. Furthermore, ABCD4 has been shown to interact with the proteins, cyanocobalamin reductase/alkylcobalamin dealkylase and cobalamin trafficking protein CblD, that help cobalamin The substrate specificities of ABCD1 and ABCD2 are overlapped.…”
Section: (See Below)mentioning
confidence: 99%